Positive correlation of ANGPTL8 expression in human visceral adipose tissue with body mass index - Chen, Shiau-Mei; Huang, Tse-Ying; Lee, Wei-Jei; Chuang, Lee-Ming; Chang, Tien-Jyun (Journal of the Formosan Medical Association, 2024)
Angiopoietin-like protein 8 (ANGPTL8) is an important regulator of lipid metabolism. We aimed to investigate the difference of ANGPTL8 expression in different depots of adipose tissues between individuals with and without obesity, and its correlation with various metabolic parameters. Subcutaneous (SAT) and visceral adipose tissue (VAT) samples were collected from patients who underwent bariatric or intra-abdominal surgery. Expression levels of ANGPTL8, monoglyceride lipase (MGL), monocyte chemoattractant protein-1 (MCP-1), leptin and adiponectin (APM1) were determined using real-time quantitative polymerase chain reaction. The correlation of ANGPTL8 expression with various metabolic parameters and other gene expression levels was analyzed using Person's correlation analysis. Logistic regression was used to establish a prediction model of obesity. Totally 330 subjects (obese: 281, non-obese: 49) were recruited. ANGPTL8 expression in VAT was significantly higher in the obesity group than in the non-obesity group (P = 0.0096). ANGPTL8 expression in VAT was positively correlated with body mass index (BMI) (r = 0.1169, P < 0.05) and was independently associated with obesity (O.R., 1.246; 95 % C.I. 1.013–21.533, P = 0.038). We also found the gene expression of ANGPTL8 in SAT and VAT was negatively correlated with APM1 expression in respective SAT and VAT. ANGPTL8 expression levels in VAT were higher in subjects with obesity, and positively correlated with BMI. This suggests a role of ANGPTL8 in the pathophysiology of obesity and may pave the way for novel treatment target of obesity.